2015
DOI: 10.1002/2014gl062972
|View full text |Cite
|
Sign up to set email alerts
|

Solar illumination control of ionospheric outflow above polar cap arcs

Abstract: We measure the flux density, composition, and energy of outflowing ions above the polar cap, accelerated by quasi-static electric fields parallel to the magnetic field and associated with polar cap arcs, using Cluster. Mapping the spacecraft position to its ionospheric foot point, we analyze the dependence of these parameters on the solar zenith angle (SZA). We find a clear transition at SZA between ∼94• and ∼107• , with the O + flux higher above the sunlit ionosphere. This dependence on the illumination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
(82 reference statements)
3
21
1
Order By: Relevance
“…This has been evidenced by many observational studies and models (Abe et al, 1993;Su et al, 1998a, b;Glocer et al, 2012;Maes et al, 2015). Maes et al (2015), studying outflow above smallscale polar cap arcs using Cluster (Escoubet et al, 2001) measurements, found that the upflow above the polar cap can be roughly divided into two distinct groups based on the solar zenith angle (SZA) of the footpoint of the field line in the ionosphere. The border between both was found to be around ∼ 100…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…This has been evidenced by many observational studies and models (Abe et al, 1993;Su et al, 1998a, b;Glocer et al, 2012;Maes et al, 2015). Maes et al (2015), studying outflow above smallscale polar cap arcs using Cluster (Escoubet et al, 2001) measurements, found that the upflow above the polar cap can be roughly divided into two distinct groups based on the solar zenith angle (SZA) of the footpoint of the field line in the ionosphere. The border between both was found to be around ∼ 100…”
Section: Introductionmentioning
confidence: 89%
“…Since precipitating electrons caused by the polar cap arc system deposit energy in the ionosphere below, this might cause concern that these flux densities are not representative of the polar wind. Maes et al (2015) argued to the contrary, since they found that the magnitude of the relatively small potential drop of the polar cap arcs (and thus the energy of the precipitating electrons) does not seem to have any discernable effect on the flux densities. The fact that the outflow is predominantly controlled by the ionospheric illumination conditions also indicates that the energy deposited in the ionosphere by precipitation in polar cap arcs plays a minor role.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations